Cover Picture: Stimulus‐Responsive Short Peptide Nanogels for Controlled Intracellular Drug Release and for Overcoming Tumor Resistance (Chem. Asian J. 7/2017). Issue 7 (22nd March 2017) - Lyu, Linna; Liu, Fang; Wang, Xiaoyong; Hu, Ming; Mu, Jing; Cheong, Haolun; Liu, Gang; Xing, Bengang
Abstract : Overcoming resistance : Multidrug resistance (MDR) remains a major problem for effective chemotherapy. In this study, a smart stimulus‐responsive self‐assembled system (PD/VER nanogel), formed from a short peptide‐Dox prodrug (PD) and the P‐glycoprotein inhibitor Verapamil (VER), was successfully developed for overcoming MDR. Such inhibitor‐encapsulated nanogels could greatly enhance the accumulation of drugs in resistant cancer cells, thereby effectively reversing tumor resistance. More information can be found in the Full Paper by Fang Liu, Bengang Xing et al. onpage 744 in Issue 7, 2017 (DOI: 10.1002/asia.201601704).